PENGEMBANG LITERASI BERBASIS BERMAIN UNTUK MENINGKATKAN KETRAMPILAN KOMUNIKATIF ANAK: PLAY-BASED LITERACY DEVELOPER TO IMPROVE CHILDREN'S COMMUNICATIVE SKILLS - Agustin, Asty; Syafila, Fitria Nala; Munawaroh, Hidayatu (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
Play-based literacy development or Learning by Playing, play is a world for children. They will recognize, perceive, and learn various things through playing. In playing activities, children build their literacy skills based on the experiences they encounter while playing, and children are even able to retell their experiences while playing. This is the essence or fundamentals of pre-literacy itself. This research aims to improve children's communicative skills by implementing a play-based literacy learning model. This type of research is descriptive research. The article process includes direct observation techniques and library research. The subject of this article is early childhood in the golden age aged 0-5 years. The results of the article show that children playing while learning in a fun and entertaining way can develop children's potential optimally. This research concludes that the use of a play-based literacy learning model can improve the quality of communicative skills in early childhood.